Integration of a Carbon Capture process in a chemical industry - Case study of a steam cracking plant - Sherif, Ahmed (My University, 2010)
One of the largest environmental challenges of modern time is to reduce the emissions of green house gases (GHG) in general, and particularly the emissions of CO2. One large source of GHG emissions is process industry. Carbon capture and storage (CCS) technologies are currently being developed to separate the CO2 from flue gases generated from combustion. Borealis site in Stenungsund is involved in an initiative that aims to reduce the CO2 emissions in the Skagerrak region with CCS technology. A post combustion carbon capture process with mono-ethanolamine (MEA) absorption is evaluated to separate CO2 from flue gases generated in Borealis’ cracker plant. The post combustion process was simulated in Aspen Plus to find the optimal operating conditions. The post combustion process is very energy demanding. To reduce the energy demand process integration possibilities with the cracker plant were investigated with help of pinch analysis. Utilizing excess heat from the carbon capture process showed substantial heat savings potentials. It was also shown that the heat saved could be used in the post combustion process. 40 MW heat representing 64 % of the carbon capture process heating demand could be saved by process integration and optimization. A study by Tel-Tek investigated the implementation of the post combustion process without process integration. In order to meet the heating demand of the process a steam boiler was proposed to supply the heat. This thesis shows that investment of a steam boiler can be avoided thanks to process integration. Compared to the study made by Tel-Tek, the investment costs for the capture plant were reduced from 114.5 M€ to 66.9 M€ and the operating costs were reduced from 24 M€/yr to 15.9 M€/yr. The resulting CO2 net capture cost was reduced from 80 €/ton CO2 to 55 €/ton CO2. It should be pointed out that the results are based on theoretical savings. Costs for retrofits should be studied in detail to assess the actual savings. Transportation and storage costs should also be considered in possible future studies.
Keywords: Kemiteknik; Chemical Engineering